A review of lahars; past deposits, historic events and present-day simulations from Mt. Ruapehu and Mt. Taranaki, New Zealand. Issue 2 (3rd July 2021) - Procter, Jonathan; Zernack, Anke; Mead, Stuart; Morgan, Michael; Cronin, Shane
ABSTRACT: Volcaniclastic diamictons, while found in all ancient and modern volcanic settings across New Zealand, are most commonly associated with stratovolcanoes. Lahar refers to a volcanic mass flow that consists of variable amounts of water and particles of different-sized volcanic lithologies; such flows can exhibit a range of rheologies that rapidly change at temporal and spatial scales. At Mt. Taranaki time packages of lahar deposits were originally grouped into chronostratigraphic formations, such as the 22, 500–11, 000 yrs B.P. Warea Formation, which consists of lahar deposits that display a range of sediment-water interactions reflecting variable rheological regimes. In historic times, lahars have been rare at Mt. Taranaki with the most recent events occurring in 1999 and 2008. In contrast, Mt. Ruapehu has been extremely active over the last 170 years with regular small-volume eruption-induced events and larger, more significant Crater-Lake breakout lahars. The Onetapu Formation comprises flows of the last 2, 000 years that are 1–2 orders of magnitude greater in volume, stage and discharge. To better understand the hazard potential of such events, a range of numerical modelling and simulations have been created, with computational simulations being applied to hindcast and forecast the potential hazards of lahars from New Zealand's stratovolcanoes.